Impact Force Identification using the Modal Transformation Method in Collocated and Non-Collocated Cases - Abdul Ghaffar, Abdul Rahman; Khoo, Shin Yee; Zubaidah, Ismail; Kong, Keen Kuan; Ong , Zhi Chao; Chong, Wen Tong; Siamak, Noroozi (Faculty Mechanical Engineering, UMP, 2014)
Previous impact force identification has focused on collocated cases because noncollocated cases tend to be ill-posed. Considering the impact location is inaccessible, impact force identification using remote responses away from the impact location must be developed. This study initiates an effort to examine impact force identification for non-collocated case. A methodology utilizing operating deflection shape analysis, modal analysis and the modal transformation method (MTM) is presented to identify the unknown dynamic force. The performance of this approach is examined via experimental verification. The objective of this study is to examine the effectiveness of impact force identification by using MTM for both collocated and non-collocated cases. By measuring the response and frequency response function of the test rig, the time history of the unknown force is recovered by the force identification method where the impact location is known. The proposed method is examined at Points 1 and 15, which have satisfactory and poor curve fitting results respectively. It is found that force accuracy improves when the curve fitting result is enhanced. Experimental results show that impact force identification via MTM is applicable in both collocated and noncollocated cases, only if the curve fitting results satisfactory.